Selection of differentiated maturity genotypes of Coffea canephora - João Felipe de Brites Senra; Viviane Alexia Correia Silva; Marlon Dutra Degli Esposti; Adésio Ferreira; Idalina Sturião Milheiros; Isabela Bolari Ramos; Rosana Gomes de Oliveira; Lorran Marques Benevenute (Acta Scientiarum: Agronomy)
The aim of this study was to select Coffea canephora genotypes from the seminal propagation variety ‘ES8152’ with different harvest times. The experiment was conducted using a Federer augmented block design with three repetitions, evaluating 175 genotypes and four clonal witnesses in two harvests (2022 and 2023), and 20 morphoagronomic characteristics were evaluated. The data were analyzed using the REML/BLUP methodology with the Selegen software, where the variance components and genetic values were estimated. The selection was performed using the Mulamba-Rank index. The bottom sieve (BS) and top sieve (TS) characteristics had high heritability (0.5779 and 0.6694, respectively) and accuracy (0.7602 and 0.8182, respectively). TS also showed high repeatability (0.6827). The genotypic effects were significant at 1% level for days for fruit ripening, fruit size, vegetative vigor, yield per plant, TS, and BS; at 5% level for general scale; and at 10% level for incidence of rust, degree of inclination, and percentage of fruit float. It was possible to distinguish 20 superior genotypes in terms of maturation, among which the selection gains for the genotypic clusters were 46.14, 45.92 and 41.56% for indefinite, early, and late maturation, respectively, by applying a selection intensity of 11.43%. Genotypes 25, 26, 73, 93, and 100 could be used for early maturing varieties, whereas genotypes 155 and 189 could be used for late-maturing varieties. The most promising genotypes for composing a variety, regardless of the maturation period, were 20, 39, 90, 112, and 190, as these were among the five best genotypes ranked in the three selection processes, demonstrating that they added superior desired morphoagronomic characteristics. It is concluded that there is genetic variability among the 175 genotypes evaluated, as well as significant genetic effects to be explored in the pool gene of individuals originating from the 'ES8152' variety.